Family Satisfaction with Care Provided in Intensive Care Unit; a Multi-Center, Cross-Sectional Study - Liyew TM; Mersha AT; Admassie BM; Arefayne NR (Patient Related Outcome Measures, 2024)
Temesgen Misganaw Liyew, Abraham Tarekegn Mersha, Belete Muluadam Admassie, Nurhusen Riskey Arefayne Department of Anesthesia, College of Medicine and Health Sciences, University of Gondar, North Gondar, EthiopiaCorrespondence: Belete Muluadam Admassie, Email uogbelete@gmail.comBackground: Healthcare provided in medical facilities should prioritize the needs of families, as it enhances the quality of care for the patients. Family satisfaction gauges how effectively healthcare professionals address the perceived needs and expectations of family members. Numerous factors, including information dissemination, communication, family dynamics, patient characteristics, hospital facilities, and the caregiving process, serve as predictors of family satisfaction. Thus, this study seeks to evaluate the satisfaction of families with the care received by patients admitted to the intensive care unit.Methods: A hospital-based cross-sectional study involving 400 participants was conducted across multiple centers from March to June 2023. Multicollinearity was assessed by examining variance inflation factors (VIF), while the goodness-of-fit was evaluated using the Hosmer and Lemeshow test. Both bivariable and multivariable logistic regression analyses were utilized to identify factors correlated with family satisfaction. Variables with a p-value below 0.2 in the bivariable logistic regression were included in the multivariable logistic regression analysis. Adjusted Odds Ratios (AORs) with 95% Confidence Intervals were computed to indicate the strength of association. In the multivariable analysis, variables with a p-value less than 0.05 were deemed statistically significant.Results: The overall family satisfaction with the care provided in the intensive care unit was 58.6%, with a 95% confidence interval ranging from 55.882% to 61.241%. Families expressed higher satisfaction levels with patient care (64.8%) and professional care (67.4%). However, they reported lower satisfaction levels regarding care provided for families (52.2%), the ICU environment (56.8%), and involvement of families in decision-making (55.8%). Lack of formal education (AOR: 1.949, 95% CI: 1.005, 4.169), completion of primary education (AOR: 2.581, 95% CI: 1.327, 5.021), and completion of grades 9– 12 (AOR: 2.644, 95% CI: 1.411, 4.952) were found to be significantly associated with overall family satisfaction.Conclusion and recommendation: The overall level of satisfaction is satisfactory. To enhance service quality and family satisfaction, healthcare providers should prioritize effective and regular communication with family members. Keeping them well informed about the patient’s condition and treatment plan is essential.Keywords: critical care, family satisfaction, intensive care unit, quality care, satisfaction